2017
DOI: 10.3892/ijmm.2017.2869
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-treated Ecklonia cava extract inhibits adipogenesis through the downregulation of C/EBPα in 3T3-L1 adipocytes

Abstract: In this study, we examined the inhibitory effects of enzyme-treated Ecklonia cava (EEc) extract on the adipogenesis of 3T3-L1 adipocytes. The components of Ecklonia cava (E. cava) were first separated and purified using the digestive enzymes pectinase (Rapidase® X-Press L) and cellulase (Rohament® CL). We found that the EEc extract contained three distinct phlorotannins: eckol, dieckol and phlorofucofuroeckol-A. Among the phlorotannins, dieckol was the most abundant in the EEc extract at 16 mg/g. Then we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 76 publications
(79 reference statements)
0
20
0
Order By: Relevance
“…Additionally, it decreased the expression of CCAAT/(C/EBP)a, SREBP-1c, adipocyte-FABP, FAS, and adiponectin. Thus, EC prevented adipogenesis by affecting the activation of the C/EBPa signaling pathway and the resulting adipogenesis-related gene expression (Kim and Nam 2017). In a similar report, dieckol from EC inhibited lipid accumulation via activation of AMPKa signaling and cell-cycle arrest in 3T3-L1 cells and mouse and zebrafish models ).…”
Section: Anti-obesity Activitymentioning
confidence: 57%
“…Additionally, it decreased the expression of CCAAT/(C/EBP)a, SREBP-1c, adipocyte-FABP, FAS, and adiponectin. Thus, EC prevented adipogenesis by affecting the activation of the C/EBPa signaling pathway and the resulting adipogenesis-related gene expression (Kim and Nam 2017). In a similar report, dieckol from EC inhibited lipid accumulation via activation of AMPKa signaling and cell-cycle arrest in 3T3-L1 cells and mouse and zebrafish models ).…”
Section: Anti-obesity Activitymentioning
confidence: 57%
“…In the present study, the hepatic expression levels of the lipid metabolism-associated genes AMPK and ACC were investigated with western blot analysis. In a previous study, EEc treatment in 3T3-L1 adipocytes reduced C/EBPα/β/δ and PPARγ levels ( 58 ). In the present study, the EHD groups had lower expression levels of C/EBPα and PPARγ compared with those in the HFD group.…”
Section: Discussionmentioning
confidence: 87%
“…Studies on the anti-obesity effects of E. cava have been performed in zebrafish ( 49 , 50 ), mice ( 51 53 ) and cell cultures ( 54 57 ), with most of these studies focusing on identifying a method to effectively extract phlorotannins (e.g., eckol, dieckol and phlorofucofuroeckol-A). For this purpose, a previous study by our group investigated a variety of methods, including hot-water extraction, ethanol extraction and enzyme extraction, and assessed the yield efficiency and economic efficiency ( 58 ). Hot water treatments (60°C and 90°C), ethanol treatments (60 and 80%) and enzymatic treatments (Protex 6L, an endo-type protease; Rapidase press L, a pectinase cellulase/hemicellulase enzyme complex; Rohament CL, a cellulase β glucanase/hemicellulase enzyme complex; and a Rapidase press L + Rohament CL complex) were performed to determine the optimal conditions for processing E. cava .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds have anti-diabetic, anti-cancer, anti-oxidant, and anti-bacterial and radioprotective properties, as well as inhibitory effects against the human immunode ciency virus (17)(18)(19)(20). A previous report showed that compounds isolated from the ethanol extract of dried E. cava (EEEC) including phloroglucinol, eckol, phlorofucofuroeckol, and dieckol exhibit strong antiviral activity against porcine epidemic diarrhea virus by inhibiting viral entry and/or replication and suppressing adipogenesis through the downregulation of C/EBPα in adipocytes (21,22). In addition, a previous report suggested that E. cava has bene cial effects on growth performance, cecal micro ora, and intestinal morphology in weaning pigs (23).…”
Section: Introductionmentioning
confidence: 99%